Pemanfaatan LMS Moodle Sebagai Media Pembelajaran Daring Bagi Santri Pondok Pesantren Tahfidzul Qur’an Wahidin Halim - Achmad Syarif; Lis Suryadi; Gandung Triyono (CV. Multi Kreasi Media, 2025)
The use of information technology in the world of education is an important need, especially in the context of online learning. The Tahfidzul Qur'an Wahidin Halim Islamic Boarding School faces challenges in organizing effective and structured online learning. This community service activity aims to introduce and implement the Learning Management System (LMS) Moodle as an online learning medium for students. The partner for this activity is the Tahfidzul Qur'an Wahidin Halim Islamic Boarding School with a total of 45 students and 5 teachers involved. The implementation method includes training, technical assistance, and evaluation through questionnaires. The results of the activity showed that 87% of participants stated that the LMS Moodle was very helpful in the online learning process, and 76% of teachers were able to independently upload materials and create discussion forums. This activity shows that the use of the LMS Moodle can increase the effectiveness and interactivity of online learning in the Islamic boarding school environment